Fluorescent cyclic voltammetry of immobilized azurin: direct observation of thermodynamic and kinetic heterogeneity. - Salverda, J; Patil, A; Mizzon, G; Kuznetsova, S; Zauner, G; Akkilic, N; Canters, G; Davis, J; Heering, H; Aartsma, T (2010)
(Figure Presented) Variations in the formal electrochemical potential (E 0) and electron-transfer rates (K 0) of the blue copper protein azurin have been directly observed. A new method, fluorescent cyclic voltammetry (FCV), was used to resolve the properties of 100-1000 proteins. On this scale, the presence of large variations in the values of both E 0 and k 0 could be established and several forms of heterogeneity were differentiated. © 2010 Wiley-VCH Verlag GmbH and Co. KGaA, Weinheim.